(untitled) (Bangladesh Journal of Pharmacology, 2019)
In this study, the effect of different extracts of Centaurea pterocaula were evaluated on 6 mm wound created by punch biopsy on the rat back. The leaves of the plant were powdered and extracted with distilled water, methanol, n-hexane and ethyl acetate. Extracts were obtained in the form of pomade with vaseline and applied topically to the wounds. The wound measurements performed on day 0, 2, 4, 6, 8, 10 and 12 and the histo-pathological examination performed on day 12. The n-hexane extract had an accelerating effect on wound healing and made a positive contribution to the healing process. In conclusion, C. pterocaula has a promising future for new drug development studies by its wound healing property. Video Clip of Methodology: Wound healing assay: 2 min 52 sec: Click to watch